Performance of the ADAPT-Treated CardioCel® Scaffold in Pediatric Patients With Congenital Cardiac Anomalies: Medium to Long-Term Outcomes - Neethling, William; Rea, Alethea; Forster, Guenther; Bhirangi, Kiran (Frontiers in Pediatrics, 2020)
BACKGROUND: A Phase II Clinical Trial reviewed the performance (morbidity and calcification) of the tissue-engineered ADAPT® bovine pericardial scaffold (CardioCel®) in pediatric patients (n=30) with congenital cardiac defects. In that study, CardioCel® demonstrated no graft-related morbidity and mortality in 25 patients, over 12 months. Five patients died due to non-graft-related events. Echocardiography revealed hemodynamically stable repairs with no calcification of the scaffold. Magnetic resonance imaging (MRI) at 12 months in 10 patients confirmed the absence of calcification. These patients were followed up for further up to 10 years. We present the results of this retrospective review of these patients that were followed for further medium to long-term results to 10 years postoperatively in these patients. METHODS: Between April 2008 and September 2009, CardioCel® was implanted in 30 patients with congenital cardiac defects. Efficacy measures included graft-related mortality, morbidity and haemodynamic abnormalities. Calcification was assessed by standard 2D-M mode echocardiography and MRI at 12 months. Medium to long-term assessment included routine clinical assessments and echocardiography. RESULTS: Median age at surgery was 18 months (27 days–13 years). Twenty-five patients (142 patient years) were followed for up to 10 years. The 10-year survival rate is estimated as 86.9% (95% CI 71.4% to 100.0%). One patient was lost to follow-up. No graft-related mortality was encountered up to 10 years. Two patients died, (pacemaker complications > 5 years and arrhythmia >7 years postoperatively). No graft failure, thromboembolic events, infections or device-related reinterventions were recorded. Non-significant residual leaks occurred in 3 patients. Echocardiography demonstrated the absence of calcification in all implants. CONCLUSION: The tissue-engineered ADAPT® bovine pericardial scaffold demonstrated excellent medium to long-term performance (up to 10 years) when used as a scaffold for repair of congenital cardiac defects in children. Durability, acellularity, biostability and non-calcifying potential of CardioCel® makes it a very attractive tissue for congenital cardiac repair procedures.